Age-related changes of choroid plexus morphology, vascularization and epithelial proliferation - Samardzija, Golub D.; Andrejic-Visnjic, Bojana M.; Djolai, Matilda A.; Ilic-Sabo, Jelena R.; Amidzic, Jelena P.; Nikin, Zoran; Rakocevic, Natali Z.; Aleksic, Nikola N.; Dolamic, Borislav E.; Vukomanovic-Djurdjevic, Biserka B. (Archives of Biological Sciences, 2021)
Paper description: Dementia is thought to begin with changes in the blood-cerebrospinal fluid barrier, which makes ageing-associated alterations of the choroid plexus (ChP) a compelling topic. This study provides a histomorphometric analysis of psammoma bodies (PBs), vasculature, amyloid deposition, and epithelium of the ChP among young, middle-aged and older individuals. Ageing was associated with an increase in the number of PBs (specifically immature forms), and a significant decrease in the vascular area, accompanied by amyloid deposition. Marked age-related changes provide a unique basis for comparison with pathological changes. Given the increase in immature PBs in the elderly, we challenge the given terminology. Abstract: The choroid plexus (ChP) is essential for brain homeostasis by regulating the secretion of the cerebrospinal fluid (CSF). Despite a substantial body of work on the pathologically alterations of the ChP, there is lack of data concerning the naturally occurring morphological changes asso-ciated with ageing. In this study, we investigated 30 human ChP tissue samples that were divided into 3 groups according to age. Morphometric analysis of psammoma bodies (PBs) on hematoxylin and eosin (H&E)-stained samples and immunohistochemical analysis of ChP were performed (using antibodies to transmembrane phosphoglycoprotein protein CD34 and nuclear protein Ki-67). Amyloid deposits were detected using Congo red staining. Middle-aged and older individuals exhibited a significantly higher numerical density (ndPB) mostly as increased immature forms, which led us to question the proposed nomenclature. The proliferation rate of the ChP epithelium did not show significant difference between groups. The vascular area was markedly decreased and accompanied by amyloid deposition in blood vessel walls. While the deposits were limited to middle-sized blood vessels in the middle-aged group, in the older group deposits were also present around small vessels. The identified major morphological alterations of ageing ChP tissue provide further understanding of disfunctions of the blood-cerebrospinal fluid barrier that underlie neurodegenerative disorders.